The Influence Of Product Attributes On Brand Preference : The Moderating Role Of Salesmanship - Siregar, Widyana Verawaty (2017)
The aim of this study is to understand how product attributes determine brand preference and to investigate the impact of utilitarian and hedonic attributes on brand preference. Furthermore, this study addresses how attitude towards brand and role of salesmanship in influencing brand preference.